(untitled) (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: This study evaluated through stereomicroscopy the effectiveness of hand and rotary instrumentation techniques, either isolated or combined, in the preparation of oval-shaped root canals. Materials and method: Thirty single-rooted human mandibular incisors were selected. After endodontic access and coronal preflaring, teeth were mounted in a modified Bramante muffle and then sectioned transversely at 3 and 6 mm from the root apex. Images of each section were made under a stereomicroscope at 30Ã— magnification. Teeth were reassembled in the muffle and divided into three groups (n=10) according to the root canal preparation technique: GI - rotary preparation with Mtwo™ basic sequence (10/.04; 15/.05; 20/.06; 25/.06), followed by Mtwo™ complementary instruments (30/.05; 35/.04; 40/.04); GII - rotary preparation with Mtwo™ basic sequence, complemented by hand instruments (#30, #35 and #40); GIII - hand instrumentation using the conventional technique (#10 to #40). All instruments were used in brushing motion. The muffles were separated again so that new images of each section could be obtained. The following parameters were evaluated in pre- and postoperative images: root canal area; perimeter; mesiodistal (MD) and buccolingual (BL) diameters; and mesial (M) and distal (D) wall thickness. Next, the values measured in post- and preoperative images were subtracted forcomparison of experimental groups. Data were analyzed using the Kruskal-Wallis test (Î±=0.05). Results: No significant difference between groups was observed for all parameters. Conclusion: There was no difference among hand, rotary, or combined instrumentation; all techniques were able to increase root canal area, perimeter, and diameter in MD and BL directions. Moreover, the amount of dentin wearon proximal root canal walls was similar for all tested groups.